An examination of the validity and reliability of the organizational structure scale in the Malaysian context : preliminary results / Yusliza Mohd. Yusoff, T. Ramayah and Hazman Shah Abdullah - Mohd. Yusoff, Yusliza; Ramayah, T.; Abdullah, Hazman Shah (Faculty of Business and Management ; UiTM Press, 2007)
Organizational structure provides the basic foundation within which an organization functions. This study focuses on the two most important aspects of structure - centralization and formalization - to keep the study simple while capturing the essence of how organizations are structured. The purpose of this study is to examine the goodness of measure (validity and reliability) of the organizational structure measure developed by Hage and Aiken {1967, 1970) who posited a five dimensions instrument. The data is drawn from a largerscale study during the preliminary phase of the data collection process. The data was collected using a structured questionnaire which was sent through mail to selected companies in the manufacturing and service sector in Malaysia, A total of 90 questionnaires were returned over a period of 12-week. The results were validated through the use of factor analysis, correlation, and reliability analysis. The factor structure of the factor analysis substantially reproduced the same dimensions as developed by Hage and Aiken. Furthermore, reliability testing showed values ranging from 0.61 to 0.87 for all dimensions and thus the instrument can be considered to sufficiently reliable. In conclusion, the analysis shows that the instrument is valid (content, construct, convergent and discriminant) as well as reliable. Implications regarding the value of conducting validity and reliability test for practitioners and researchers are discussed.